SOSIALISASI EDUWISATA BATIK KEPADA UMKM BATIK DESA MUNCAR KABUPATEN SEMARANG - Suryaningsih, Sukarni; Wilujeng, Sri Rahayu; Wulandari, Retno (Harmoni: Jurnal Pengabdian Kepada Masyarakat, 2025)
Batik is a unique identity for a region which can even represent a country. This unique identity will highlight the local wisdom owned by each region and introducing batik means introducing local wisdom to a wider scale. Each pattern created always reflects special symbols or meanings that the creator wants to convey. Efforts to preserve batik can be done using various methods, one of which is done by Desa Wisata Muncar Susukan Kabupaten Semarang through organizing educational tours about batik. Batik educational tourism programs organized by UMKM in Desa Wisata Muncar which are integrated with educational tourism about the environment and community culture, could be a good option to develop in rural areas. Through batik educational tourism efforts, preserving traditions as well as stimulating the village economy can be achieved.Key words : batik, umkm, Muncar Susukan, eduwisata